Exit exams and high school dropout - Dave E. Marcotte (Institute for the Study of Labor (IZA), 2011)
In this paper, I consider the impact of the expansion of exams students must pass in order to graduate high school on dropout rates. Exit exams, as these tests are known, have become more common, and more difficult. These exams are controversial, with opponents claiming they drive marginal students out of school, and proponents arguing they align student interests with those of the school and encourage teachers and administrators to provide effort and resources on the students' behalf. I make use of the fact that when states implement exit exams, they first affect a specific graduating class. So in some states, some students in high school are required to pass these exams, while students in the grade above are not. Using a state-grade panel constructed from the Common Core of Data I find evidence that the recent expansion of exit exams has resulted in a modest increase in high school dropout rates in the aggregate, but a large increase among students in 12th grade, where additional attempts to pass exams are not possible. I also find that a policy often used to limit the impacts of exit exams on high school completion has only limited effect: Dropout rates in states where students can earn a diploma or credential even when unable to pass exit exams, dropout increases in 12th grade at about the same rate as in other states without such alternative pathways. This suggests that at least some of the impact is due to stop-out on the part of students.
urn:nbn:de:101:1-201104114015
Keywords: I2; I28; 330; high school dropout; exit exams; accountability; attainment